The impact of access to climate services on smallholder farmers' cropping decisions and household food security in Elundini municipality, Eastern Cape province - Nocezo, Yanga-Inkosi; Manyike, Jabulile Zamokuhle; Zhou, Leocadia; Ngarava, Saul (Frontiers in Climate, 2024)
The study assesses how access to climate services influences cropping decisions and, subsequently, household food security. Employing a cross-sectional research design, the study surveyed a total of 217 smallholder crop farmers selected through a multistage sampling approach. Data were collected using a semi-structured questionnaire, and both descriptive statistics and a propensity score matching (PSM) model were employed for data analysis. Household food security was assessed using households' dietary diversity. The study's findings highlight that 69% of the surveyed farmers had access to weather forecasts, while only 24% had access to seasonal forecasts. Consequently, farmers with access to climate services exhibited changes in their farming decisions, including daily farming activities, planting timing, crop selection, and land preparation. Notably, approximately 35% of the respondents were identified as food insecure. The application of the propensity score matching model revealed that access to climate services had a statistically significant positive impact on farmers' decision-making processes and household food security. These results underscore the potential of climate services to enhance farmers' decision-making capabilities and, subsequently, improve household food security. Considering these findings, it is recommended that efforts to expand access to climate services among smallholder farmers in South Africa should be intensified. This can be achieved by developing and disseminating more accessible and tailored climate information, including seasonal forecasts. In addition, initiatives should ensure that climate services are integrated into agricultural extension services and support systems to equip farmers with the knowledge and tools they need to make informed decisions.